International Capital Markets : Developments and Prospects - Mathieson, Donald; Kalter, Eliot; Kincaid, G.; Watson, Maxwell (Washington, D.C. : International Monetary Fund, 1986)
This paper provides a description and analysis of recent developments in international capital markets and an assessment of the prospects for private financing flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet